Use of solar energy in agricultural production and processing - Poonia, Surendra; Jain, Dilip; Santra, P.; Singh, A. K. (Indian Farming, 2018)
These solar photovoltic and thermal devices will be very useful in increasing crop production, processed product and milk production in addition to supplementing conventional energy sources. These devices will ensure increased farmers’ income by carrying out integrated activities. Last but not the least there will be reduction of CO2 emission to a great extent. The scope of solar thermal energy in agricultural production and processing sectors is tremendous. It can supplement conventional energy sources to a great extent to make the arid zone more self-dependent on energy. The use of renewable energy will not only curtail the consumption of fast depleting conventional fuels but also reduce greenhouse gas emissions. There is a great need of promoting the solar thermal energy by disseminating these eco-friendly technologies for the sustainable development of society. It requires active participation of users/industrialist and researchers. The availability of clean and green energy source in rural areas would enable farmers to accrue higher monetary benefits through processing and agrobased industries to improve the livelihood of farmers and enhancing their standard of living.